2021
DOI: 10.3389/fmed.2021.770343
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Endotypes of Hospitalized COVID-19 Patients

Abstract: Background: Characterization of coronavirus disease 2019 (COVID-19) endotypes may help explain variable clinical presentations and response to treatments. While risk factors for COVID-19 have been described, COVID-19 endotypes have not been elucidated.Objectives: We sought to identify and describe COVID-19 endotypes of hospitalized patients.Methods: Consensus clustering (using the ensemble method) of patient age and laboratory values during admission identified endotypes. We analyzed data from 528 patients wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 39 publications
1
19
0
1
Order By: Relevance
“…Coronavirus disease 2019 (COVID- 19), which is caused by the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), has infected more than 130 million people worldwide. COVID-19 leads to respiratory manifestations that can range from mild flu-like symptoms such as fever, cough, and fatigue to severe respiratory failure requiring intensive care (1,2).…”
Section: Introductionmentioning
confidence: 99%
“…Coronavirus disease 2019 (COVID- 19), which is caused by the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), has infected more than 130 million people worldwide. COVID-19 leads to respiratory manifestations that can range from mild flu-like symptoms such as fever, cough, and fatigue to severe respiratory failure requiring intensive care (1,2).…”
Section: Introductionmentioning
confidence: 99%
“…Following the method of Ranard et al [ 11 ] for a data set limited to November 2020 through November 2021, this study finds minimal quantitative differences with the conclusion of Ranard et al [ 11 ] that the most commonly cited comorbidities do not per se substantially increase the risk of serious consequences of SARS-CoV-2 infections. However, one cannot ignore that many persons with such conditions frequently have multiple cofactors and have either an inherent or medication-depressed level [ 37 ] of immune function that can worsen the effects of a COVID-19 infection.…”
Section: Discussionmentioning
confidence: 50%
“…A recent study of four unique endotypes of patients hospitalized with COVID-19 infections found that high-level comorbidities did not associate with poor outcome endotypes [ 10 , 11 ]. Previously, a study on the proximate and underlying causes of death as determined by the autopsy of 26 hospitalized patients found that death was “directly related to COVID-19 in the majority of patients.” Pre-existing health conditions had only contributory implications, and death was not an immediate result of those comorbidities [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Skin manifestations of COVID-19 include vesicular, urticarial, and maculopapular eruptions and livedo, necrosis, and other vasculitis forms 15 and are more common among European and North Americans than among Asians 16 . The heterogeneity of COVID-19 warrants the elucidation of the phenotypes and endotypes of COVID-19 that will benefit from precision medicine 17,18 . In addition, persistent symptoms such as fatigue, brain fog, body aches, and loss of smell may persist for months following acute infection and are referred as post-acute COVID-19 syndrome or long-COVID 19,20 .…”
Section: Clinical Characteristics Of Covid-19mentioning
confidence: 99%